The corporate governance structures of GLCs and NGLCs and firm performance in Malaysia / Azmi Abd. Hamid - Abd. Hamid, Azmi (Research Management Institute (RMI), 2011)
This study examines the relationship between corporate governance structures and the performance of matched-pairs of Government Linked Companies (GLCs ) and Non-Government Linked Companies INGLCs). The empirical results indicate that there are eight statisticallv significant differences between the corporate governance structures of GLCs and NGLCs, thus providing a rationale for examining the association between corporate governance structure and firm performance of these two distinct groups. Accordingly, univariate and multivariate analyses were performed on two sample sets: GLCs and NGLCs. In the univariate analysis, only Board size (BSZ) exhibited a significant relationship with respect to firm performance, in contrast the multivariate analysis found no empirical evidence of a consistent relationship between corporate governance structure and performance, which was measured in relation to return On Assets (ROA) and Return On Equity (ROE) in GLCs and NGLCs over the same period. Statistically significant relationships were found across groupings and for different performance measures, but were not sustained across all the years considered. The results indicate that despite the identification of eight differences in the governance structures of GLCs and NGLCs, the observed differences in firm performance cannot be explained by governance structure. This finding supports the view that governance structures purely provide appropriate means to monitor company management rather than improve performance.